Integer Linear Programming Model for Multicast Routing to Minimize Link Cost at Wavelengths - Fitria, Rizka; Suwilo, Saib; Rosmaini, Elly (Politeknik Ganesha Medan, 2023)
Routing is a technique or process carried out in a packet or information delivery system from a source to a destination or a place that requests the information needed from a source. Routing is done in solving a problem and is well-known is unicast routing. Unicast routing can transmit information from a source to a single destination. However, this is ineffective for an infinite number of requests to be served because the unicast routing system only funnels one destination to one source. So that another route is needed that can handle this, this route is called a multicast route. Multicast routing that can serve multiple destinations with only one source so that a collection of destinations to get the same request in the same time and data. This research will discuss multicast routing to minimize link costs at wavelengths using a hierarchical structure. To help provide reduction or savings on the link by offering an integer linear programming model formulation to minimize link costs at wavelengths. An update from previous studies is to use a hierarchical structure with wavelength conversion taking into account the links that are traversed and the requests that will be served by the source to the destination. Using wavelength conversion so that there are no wavelength continuity problems, so that when sending information you get more path choices and you can save on sending information using a link that will be passed from the source to the intermediate node until it reaches the destination node, with this it will find a path more efficiently so that the goal of minimizing link cost at wavelengths on multicast routing is achieved